Genetic Diversity and Molecular Evolution of Hepatitis E Virus Within the Genus Chirohepevirus in Bats - Wang, Bo; Cronin, Peter; Mah, Marcus G.; Yang, Xing-Lou; Su, Yvonne C. F. (Viruses, 2025)
Hepatitis E virus (HEV) is a major zoonotic pathogen causing hepatitis E, with strains identified in various animal species, including pigs, wild boar, rabbits, deer, camels, and rats. These variants are capable of crossing species barriers and infecting humans. HEV belongs to the family Hepeviridae, which has recently divided into two subfamilies: Orthohepevirinae and Parahepevirinae, and five genera: Paslahepevirus, Avihepevirus, Rocahepevirus, Chirohepevirus, and Piscihepevirus. Recent advances in high-throughput sequencing, particularly of bat viromes, have revealed numerous HEV-related viruses, raising concerns about their zoonotic potential. Bat-derived HEVs have been classified into the genus Chirohepevirus, which includes three distinct species. In this study, we analyzed 64 chirohepevirus sequences from 22 bat species across six bat families collected from nine countries. Twelve sequences represent complete or nearly complete viral genomes (>6410 nucleotides) containing the characteristic three HEV open reading frames (ORFs). These strains exhibited high sequence divergence (>25%) within their respective host genera or species. Phylogenetic analyses with maximum likelihood methods identified at least seven distinct subclades within Chirohepevirus, each potentially representing an independent species. Additionally, the close phylogenetic relationship between chirohepevirus strains and their bat hosts indicates a pattern of virus–host co-speciation. Our findings expand the known diversity within the family Hepeviridae and provide new insights into the evolution of bat-associated HEV. Continued surveillance of chirohepevirus will be essential for understanding its potential for zoonotic transmission and public health risks.